Respon Pertumbuhan Bibit Kelapa Sawit (Elaeis Guineensis Jacq.) Pembibitan Main Nursery terhadap Pemberian Pupuk Urea KCL dan Pupuk Kandang Ayam. - Sugito Loso; Haris Kriswantoro (Lembaga Pengembangan Kinerja Dosen, 2025)
Oil palm plants (Elaeis guineensis Jacq.) are one of Indonesia's leading commodities which have quite high productivity as a producer of vegetable oil, as well as being a source of foreign exchange for the country and employment for the community. The aim of the study was to determine the effect of urea, KCl and chicken manure on the growth of oil palm seedlings. The research location was conducted on Jalan Tapak Lebar I Rt.04, Sidorejo Village, Lubuklinggau Barat II District, Lubuklinggau City, South Sumatra, from September to December 2024. Treatment P1 = No treatment, P2 = Urea fertilizer 5 g/plant, P3 = KCl fertilizer 5 g/plant, P4 = Chicken manure 250 g/plant, P5 = Urea fertilizer 5 g + KCl 5 g/plant, P6 = Urea fertilizer 5 g + chicken manure 250 g/plant, and P7 = KCl fertilizer 5 g + chicken manure 250 g/plant. Each sample treatment consisted of 3 seedlings and was repeated 3 times. Using a non-factorial Completely Randomized Design (CRD), Duncans Multiple Range Test (DMRT). The administration of urea fertilizer at a dose of 5 g/plant and chicken manure at a dose of 250 g/plant gave the best effect on all observation variables, namely: increase in height, increase in the number of leaf stalks, stem diameter, number of leaflets, length of leaflets.